A secure and resilient cross‐domain SIP solution for MANETs using dynamic clustering and joint spatial and temporal redundancy‡. (2nd December 2016) - Aburumman, Ala'; Seo, Wei Jye; Esposito, Christian; Castiglione, Aniello; Islam, Rafiqul; Choo, Kim‐Kwang Raymond
Summary: In this paper, we extend our earlier work (where we presented a cross‐domain Session Initiation Protocol solution for mobile ad hoc networks using dynamic clustering) to handle packet losses affecting wireless networks and deal with outbound requests using reputation method. The (extended) solution is designed also to avoid the inherent shortcomings associated with centralized approaches (e.g. single point of failure). Using simulations, we evaluate the extended solution under different conditions. Findings from the evaluations demonstrate the utility of our solution. Copyright © 2016 John Wiley & Sons, Ltd.